Innovative Approaches to Preventing Major Industrial Accidents: A Comprehensive Custom Risk-Specific HSSEQ Management Framework - Bahar, Zeynep; Havva, Duygu Bilgen; Orcun, Sarioguz (International Journal of Scientific Research and Management (IJSRM), 2025)
The problem of industrial accidents is still one of the most worrying issues in the global context, where each year, workplace accidents take more than 2.3 million lives and bring extensive financial losses. The study establishes new mechanisms of prevention of major industrial accidents using an extensive Health, Safety, Security, Environment, and Quality (HSSEQ) management concept. The research combines behavior-based safety systems, new digital technologies, and tailor-made protocols that are specific to a risk. By analyzing implementation data collected in various industrial branches, the study will show that the implementation of this system can bring the total number of workplace incidents down to 96 percent and save millions of dollars, as it amounts to USD 1.7 million on average when 200,000 work hours are performed. The results indicate that it is possible to integrate digital solutions with the principles of behavioral science to make the safety management system more resilient and responsive, which can help overcome complex risks present within industries.